GREEN TECHNOLOGY IN IMPROVING DEFECT MANAGEMENT MODEL FOR OPERATED HERITAGE BUILDINGS IN MALAYSIA– A LITERATURE REVIEW - Ahmad Mu’az; Mohd Azian Zaidi; Nur Azfahani Ahmad (Journal of Islamic, Social, Economics and Development, 2021)
Heritage buildings are prone to many issues related to humidity, such as condensation, lack of air circulation, mould growth and poor air quality that will affect the building life span. At the moment, more than 300 heritage buildings in Malaysia are exposed to these conditions, whilst still maintained conventionally. In conjunction with the Malaysia Science, Technology, Innovation and Economy (MySTIE), the Shared Prosperity Vision 2030 (SPV 2030) and the United Nation Sustainable Development Goals (SDGs), it is significant to establish sustainable heritage buildings through various efforts of defect management models. However, at present, these models are lacking in finding the significant solutions in controlling defect issues that are related to internal-humidity conditions for heritage buildings that empowered by green technologies. Most of the defect management models found in Malaysia are related to typical procedures and generic documentation. Relevant to the Fourth Industrial Revolution (IR 4.0), Malaysia have significant potential in establishing a new defect management model that can be linked with green technologies. Since Malaysia receives abundant energy from solar, initiating green technologies which based from solar energy is highly recommended. This can be an alternative for providing energy for relevant mechanism in improving defect based-humidity, such as ventilators or turbines. This research tries to explore the key factors on how these green technologies can help to associate and improve defect management techniques in heritage buildings. Through literature review, it will focus on heritage buildings that have significant defect issues in order to formulate a significant defect management model that can be integrated with green technologies. Ideally, this model can be used by the Government to establish a more sustainable heritage buildings and ultimately, improved the defect management models in Malaysia that are relevant to IR 4.0.